Small animal medicine and metabolic disorders : self-assessment color review - Ruaux, Craig (Boca Raton : CRC Press, Taylor & Francis, 2018)
Key features: Includes over 150 new, color illustrated cases Covers all aspects of diseases and disorders and affecting organs of the abdominal cavity and the endocrine/metabolic system Written by experts from the USA, Australia, the United Kingdom, and Europe Nearly 20 years after Bryn Tennant's first edition, this newupdate covers all aspects of diseases and disorders and affecting organs of the abdominal cavity and the endocrine/metabolic system in a case-based format.Responding to advances in imaging technology, digital radiography and high-resolution ultrasonography as well as the growth in specialised diagnostic tests for many diseases, neweditor Craig Ruaux brings together a wide variety of new cases. These cases cover a wide spectrum of metabolic, endocrine, immune-mediated, inflammatory and infectious diseases and range in difficulty from simple bacterial infections to complex, multisystem disorders that would challenge most practitioners.They are presented in random order, as they would appear in everydaypractice, and each author brings their own specialistexpertise and experience to problem identification and management. Presenting an assortment of cases and case-related materials appropriate to the day-to-day practice of small animal medicine, this book will be an essential reference for veterinary students of internal medicineas well asspecialists in training.
Preceded by Self-assessment colour review of small animal abdominal and metabolic disorders / [edited by] Bryn Tennant. c1999.
OCLC-licensed vendor bibliographic record.
Keywords: Dogs -- Diseases; Cats -- Diseases; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; MEDICAL / Veterinary Medicine / Food Animal